A SYSTEMATIC LITERATURE REVIEW ON THE EFFECTIVENESS OF THE PROJECT-BASED LEARNING MODEL IN MATHEMATICS EDUCATION - Zulbaida Zulbaida; Nailul Authary (Jurnal Ilmiah Pendidikan dan Pembelajaran Matematika, 2025)
This study aims to systematically review the effectiveness of the Project-Based Learning (PjBL) model in mathematics education. The research employed a Systematic Literature Review (SLR) method by analyzing relevant journal articles and conference proceedings published between 2018 and 2024. The literature search was conducted using several databases, including Google Scholar, ERIC, Semantic Scholar, ResearchGate, and university repositories. The selected studies met predefined inclusion criteria, covering educational levels from elementary school to higher education, and employing qualitative, quantitative, or mixed-method research designs.The analysis of 18 selected studies indicates that Project-Based Learning is consistently effective in improving mathematics learning outcomes, particularly in terms of academic achievement, conceptual understanding, critical and creative thinking skills, learning motivation, and student engagement. The majority of studies were conducted at the elementary and junior high school levels, with quasi-experimental and experimental designs being the most commonly used. However, several challenges were identified, including time constraints, teacher readiness, and limited learning resources.Overall, Project-Based Learning is recommended as an innovative, student-centered approach to mathematics instruction and is well aligned with the principles of the Merdeka Curriculum. The findings of this review are expected to serve as a reference for educators and researchers in designing more contextual and meaningful mathematics learning strategies.